Pre‐diagnostic derivatives of reactive oxygen metabolites and the occurrence of lung, colorectal, breast and prostate cancer: An individual participant data meta‐analysis of two large population‐based studies. Issue 1 (5th January 2019) - Gào, Xīn; Wilsgaard, Tom; Jansen, Eugène HJM; Holleczek, Bernd; Zhang, Yan; Xuan, Yang; Anusruti, Ankita; Brenner, Hermann; Schöttker, Ben
Abstract : Oxidative stress may be involved in carcinogenesis and biomarkers of oxidative stress like derivatives of reactive oxygen metabolites (d‐ROM) may be useful for cancer prediction. However, no previous study assessed the association of pre‐diagnostic d‐ROM measurements with cancer incidence. We measured serum d‐ROM levels in a cohort sample of n = 4, 345 participants of the German ESTHER study and in a case‐cohort sample of the Norwegian Tromsø study (cancer cases: n = 941; subcohort: n = 1, 000). Moreover, d‐ROM was repeatedly measured at follow‐ups of both studies. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were derived by (weighted) multivariable‐adjusted Cox regression with time‐dependent modeling of d‐ROM levels for incident lung, colorectal, breast and prostate cancer. Individual study results were pooled by random effects meta‐analysis. The HRs (95% CI) for comparison of top and bottom d‐ROM tertile were statistically significant for lung (1.90 [1.25–2.89]), colorectal (1.70 [1.15–2.51]) and breast cancer incidence (1.45 [1.01–2.09]) but not for prostate cancer incidence (1.20 [0.84–1.72]). In conclusion, this individual participant data meta‐analysis of two large population‐based cohort studies with repeated d‐ROM measurements yielded evidence for an involvement of high oxidative stress in carcinogenesis. Given the observed associations of pre‐diagnostic d‐ROM measurements with lung, colorectal and breast cancer incidence, subjects with increased serum d‐ROM levels should be recommended to reduce these levels by lifestyle changes including smoking cessation, a healthy diet and an increase in physical activity. Abstract : What's new? Oxidative stress is a well‐established cancer risk factor but reactive oxygen species are difficult to measure in patients because of a short half‐life. Here the authors focused on serum derivatives of reactive oxygen metabolites (d‐ROM), a more stable proxy for reactive oxygen species. By combining data from two large, population‐based cohort studies from Germany and Norway, they found that high d‐ROM levels were strongly associated with lung, colorectal and breast, but not prostate cancer, findings with potential implications for lifestyle changes in the affected individuals.